Improved Sensitivity of Ultrasound‐Based Subharmonic Aided Pressure Estimation Using Monodisperse Microbubbles. (1st November 2021) - van Hoeve, Wim; de Vargas Serrano, Miguel; te Winkel, Lisa; Forsberg, Flemming; Dave, Jaydev K.; Sarkar, Kausik; Wessner, Corinne E.; Eisenbrey, John R.
Abstract : Objectives: Subharmonic aided pressure estimation (SHAPE) has been shown effective for noninvasively measuring hydrostatic fluid pressures in a variety of clinical applications. The objective of this study was to explore potential improvements in SHAPE sensitivity using monodisperse microbubbles. Methods: Populations of monodisperse microbubbles were created using a commercially available microfluidics device (Solstice Pharmaceuticals). Size distributions were assessed using a Coulter Counter and stability of the distribution following fabrication was evaluated over 24 hours. Attenuation of the microbubble populations from 1 to 10 MHz was then quantified using single element transducers to identify each formulation's resonance frequency. Frequency spectra over increasing driving amplitudes were investigated to determine the nonlinear phases of subharmonic signal generation. SHAPE sensitivity was evaluated in a hydrostatic pressure‐controlled water bath using a Logiq E10 scanner (GE Healthcare). Results: Monodisperse lipid microbubble suspensions ranging from 2.4 to 5.3 μm in diameter were successfully created and they showed no discernable change in size distribution over 24 hours following activation. Calculated resonance frequencies ranged from 2.1 to 6.3 MHz and showed excellent correlation with microbubble diameter ( R 2 > 0.99). When investigating microbubble frequency response, subharmonic signal occurrence was shown to begin at 150 kPa peak negative pressure, grow up to 225 kPa, and saturate at approximately 250 kPa. Using the Logiq E10, monodisperse bubbles demonstrated a SHAPE sensitivity of −0.17 dB/mmHg, which was nearly twice the sensitivity of the commercial polydisperse microbubble currently being used in clinical trials. Conclusions: Monodisperse microbubbles have the potential to greatly improve the sensitivity of SHAPE for the noninvasive measurement of hydrostatic pressures.